Adaptive Network Architectures for Disaster Recovery and Operational Continuity in Semiconductor Infrastructure - Kishor Kumar Bhupathi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The article explores how adaptive network architectures are changing the semiconductor industry, looking at their effects on production, technology and supply chain. Growing use of semiconductor parts in many fields makes it very important to have reliable digital infrastructure. The paper sets out an adaptive network architecture system made for semiconductor environments that helps operations keep going both during small and widespread disruptions. Because of Software-Defined Networking (SDN), Network Function Virtualization (NFV), Digital Twin technology and AI, the network can fix problems by itself as it happens. By using edge-reliable systems and routing set by intentions, the framework can decide on the best way to use resources and choose network paths in factories, data centers and all parts of the supply chain. Simulation tests indicate that downtime is decreased by 68% and there is an 80% improvement in keeping operations running without disruptions during a series of failure events. Addressing the specific operational concerns in semiconductor production, like fast response time, predictable timing and security, this framework allows others to improve supply chain security and provides a key base for future advancements in semiconductors.
Keywords: Adaptive Network Architecture; Semiconductor Manufacturing; Software-Defined Networking; Network Function Virtualization; Digital Twin technology; AI-enabled predictive analytics; edge-resilient networks; Operational Continuity; Supply Chain Resilience